El problema de los opuestos bajo la forma de la contradicción en la filosofía de Nietzsche - Leyva Zegarra, Vanessa Elsie (2019)
This article delves into the problem of contradiction in Nietzschean philosophy, taking Müller-Lauter’s interpretation as the main reference. Its main objective is to shed light on the path followed by Nietzsche towards the postulation of the will to power as a perspectivist reading of reality, which replaces the traditional notion of metaphysical truth. The argument focuses on refuting the equalization of Nietzschean perspectivism with the arbitrariness of a crude relativism, by examining the relationship between the will to power and the will to truth.